Revealing faces: Gender and cultural differences in facial prominence of selfies - Čuš Babič, Nenad (PLoS One, 2018)
An international sample of 2754 selfies uploaded to Instagram that form part of the Selfiecity (www.selfiecity.net) research project (selfies originating from Bangkok, Berlin, London, Moscow, New York, and Sao Paolo) were examined to assess the existence of facial prominence differences in depictions of males and females and the variability of facial prominence among cultures. Results show that gender stereotypical bias resulting in greater facial prominence in depictions of men is present in selfies. The control of image creation and selection for publication by the persons presented in the images do not diminish this gender based bias. Also, when gender is controlled, significant differences exist in facial prominence among different cultures. Comparisons with various socio-cultural indicators indicate possible correlations of gender stereotypical bias to self-expression values, freedom of choice, people’s influence on government’s decisions, protection of freedom of speech and people’s influence on issues in the professional and communal environment. This research does not find a correlation of gender based bias in selfies with gender equality or inequality measures among cultures.